Impact of solar shading geometry on building energy use in hot humid climates with special reference to Malaysia - R. Ossen, Dilshan; Ahmad, M. Hamdan; Madros, Nor Haliza (2005)
External solar shading devices can substantially reduce the cooling load of buildings and large energy savings can be achieved. Hence, intercepting the radiant heat wave before penetrating to the internal environment through envelope openings is the main criterion in designing solar shading. In hot and humid climate, one draw back of using shading devices is the risk to reduce daylight level thus increases in use of artificial lighting. Therefore it is important to understand the magnitude of energy consumption for cooling and lighting when shading devices are adapted in order to analyze optimum shading as energy conservation option in high-rise office buildings. In other words, little is known about the relationship between energy use and external horizontal shading device geometry. In an attempt to elucidate these complex relationships, a simple experiment of an office room is carried out using dynamic computer simulation program eQUEST- 3 (DOE 2.2). The study indicated depth of the external horizontal overhang can be manipulated to obtain an optimum energy use in high-rise buildings. The results showed that correlation between overhang depth and energy is an important aspect compared to correlation between overhang depth with building cooling loads and daylight level, especially in tropical climate conditions.